THU0638 CONSIDERATIONS FOR IMPROVING QUALITY OF CARE IN RHEUMATOID ARTHRITIS AND ASSOCIATED COMORBIDITIES. (June 2019) - Kvien, Tore K.; Pavelka, Karel; Polido-Pereira, Joaquim; Semb, Anne Grete; Sköld, Magnus; Balsa, Alejandro; Betteridge, Neil; Buch, Maya; Durez, Patrick; Favalli, Ennio; Favier, Guillaume; Gabay, Cem; et al.
Abstract : Background: The presence of comorbidities in patients with rheumatoid arthritis (RA) contributes to increased morbidity and mortality (1) . Patients with RA have an increased risk of comorbidities e.g. interstitial lung (IL) disease (7.7% incidence (2) ; up to 60% IL abnormalities in early RA (3) ), depression (up to 200% (4) ; 16.8% (5) ), cardiovascular disease (40-70% (6) ; 5-12.9% (7) ) and diabetes (IR of 8.6 per 1000 person-years (8) ; 20% (9) ). Yet, there are few comprehensive recommendations on the management of RA-related comorbidities. Objectives: This study aimed to identify models of good quality care for patients with RA and their associated comorbidities in Europe and understand how these practices can be widely implemented. Methods: Existing published recommendations across Europe on good practice in RA care including screening/managing selected comorbidities were reviewed. Team members of 12 specialist centres across Europe were interviewed. The interventions identified were reviewed and prioritised to form a selection of considerations by a consensus process involving 18 experts including rheumatologists, a patient rep., a nurse and also RA comorbidity specialists: cardiologist, psychologist, pulmonologist and diabetologist. Results: The interventions were prioritised for each patient profile: suspected RA: rapid access to care (online referral, triage, ultrasound–guided diagnosis) enhanced communication with primary care (hotline, education sessions) early arthritis clinic (timely clinical assessment and diagnosis) recently diagnosed: enabling self–management (self–monitoring and disease activity management support) early arthritis clinic comprehensive comorbidity assessment (standalone or in conjunction with RA appointment) established disease: dedicated comorbidity specialist integrating patient registries into daily clinical practice enabling self–management Eleven other interventions were identified including task-shifting to non-physician healthcare professionals, tailored education to patients and family members, and developing care networks. Conclusion: Despite limited European recommendations on management of RA comorbidities, a range of good practice care model interventions across Europe were identified which are non-complex, high-impact and meaningful. Next step will be to assess how these care models can be implemented in different healthcare systems for the benefit of patients with RA. References: [1] Dougados, et al. Ann Rheum Dis2014; 73:62 [2] Bongartz, et al. Arthritis Rheum2010; 62(6):1583 [3] Reynisdottir, et al. Arthritis Rheum2014; 66:31 [4] Sheehy, et al. Rheum2006; 45(11):1325-1327 [5] Matcham, et al. Rheumatology2013; 52:2136 [6] Holmquist, et al. Ann Rheum Dis2017; 76:1642 [7] Van Halm, et al. Ann Rheum Dis2009; 68(9):1395 [8] Solomon D, et al. Ann Rheum Dis2010; 69(12):2114 [9] Albrecht K, et al. Rheum2018; 57(2):329-336 Disclosures: Most authors have received funding from the industry including Sanofi Genzyme who solely funded this study Disclosure of Interests: Tore K. Kvien Grant/research support from: AbbVie, BMS, MSD, Pfizer, Roche and UCB., Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Hospira, Merck-Serono, MSD, Novartis, Oktal, Orion Pharma, Pfizer, Roche, Sandoz, Sanofi, Mylan and UCB, Speakers bureau: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Hospira, Merck-Serono, MSD, Novartis, Oktal, Orion Pharma, Pfizer, Roche, Sandoz, Sanofi and UCB, Karel Pavelka: None declared, Joaquim Polido-Pereira: None declared, Anne Grete Semb: None declared, Magnus Sköld: None declared, Alejandro Balsa Grant/research support from: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Consultant for: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Sandoz, Lilly, Paid instructor for: Pfizer, Speakers bureau: Pfizer, Novartis, UCB, Nordic, Sanofi, Sandoz, Lilly, Neil Betteridge Consultant for: Amgen, Eli Lilly, Grunenthal, GSK, Heart Valve Voice, Janssen, Roche, Sanofi Genzyme and Sanofi Regeneron, Speakers bureau: Amgen, Eli Lilly, Grunenthal, GSK, Heart Valve Voice, Janssen, Roche, Sanofi Genzyme and Sanofi Regeneron, Maya Buch Grant/research support from: Pfizer LTD, UCB, Consultant for: AbbVie, Eli Lilly, EMD Serono, Pfizer Ltd., Sanofi, Patrick Durez Speakers bureau: Bristol-Myers Squibb, Eli Lilly, Sanofi, Celltrion, Ennio Favalli: None declared, Guillaume Favier: None declared, Cem Gabay Grant/research support from: Roche, Pfizer, AB2 Bio Ltd, Consultant for: Roche, Pfizer, Lilly, AbbVie, Sanofi, Regeneron, Bristol-Myers Squibb, Novartis, UCB, AB2 Bio Ltd, Debiopharm, Rinie Geenen: None declared, Ioanna Gouni-Berthold: None declared, Frank van den Hoogen: None declared, Alison Kent: None declared, Lars Klareskog Grant/research support from: Yes, but not for the presented study., Mikkel Ǿstergaard Grant/research support from: Abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, maxime dougados Grant/research support from: Eli Lilly and Company, Pfizer, AbbVie, and UCB Pharma, Consultant for: Eli Lilly and Company, Pfizer, AbbVie, and UCB Pharma